2018
DOI: 10.1186/s40900-018-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

People with lived experience (PWLE) of depression: describing and reflecting on an explicit patient engagement process within depression research priority setting in Alberta, Canada

Abstract: Plain English summaryThe Alberta Depression Research Priority Setting Project aimed to meaningfully involve patients, families and clinicians in determining a research agenda aligned to the needs of Albertans who have experienced depression. The project was modeled after a process developed in the UK by the James Lind Alliance and adapted to fit the Alberta, Canada context. This study describes the processes used to ensure the voices of people with lived experience of depression were integrated throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…Similar findings have been found in peer engagement for youth program development [17]. Among adults, patient involvement in mental health and substance use settings reduced hospital readmission, increased patient well-being and engagement, and provided educational opportunities to health care staff and systems [18][19][20][21][22][23][24][25][26]. Lastly, several studies identified the importance of developing new processes of patient-oriented care, with the help of PWLE, rather than using existing practices with the hope that patients will adapt [27,28].…”
Section: Introductionmentioning
confidence: 63%
“…Similar findings have been found in peer engagement for youth program development [17]. Among adults, patient involvement in mental health and substance use settings reduced hospital readmission, increased patient well-being and engagement, and provided educational opportunities to health care staff and systems [18][19][20][21][22][23][24][25][26]. Lastly, several studies identified the importance of developing new processes of patient-oriented care, with the help of PWLE, rather than using existing practices with the hope that patients will adapt [27,28].…”
Section: Introductionmentioning
confidence: 63%
“…Similar to a study which engaged people with the lived experience of depression in interdisciplinary research priority setting (Breault et al., 2018), critical reflection indicated that the consumer engagement for this review enriched data analysis and challenged clinician and researcher stereotypes. The health professional authors needed to consciously and conscientiously step back and share power with the consumers who ensured that the thematic analysis was reflexive and deeper, with theme names better illustrating shared meaning as recently recommended by Braun and Clarke (2019).…”
Section: Discussionmentioning
confidence: 86%
“…The benefits to researchers from partnerships with consumers include enhanced knowledge of consumer engagement, improved lay communication skills, and more positive attitudes to involving consumers (Harrison et al., 2019; Haywood, Martinez, Pyatak, & Carandang, 2019). Positive impacts for consumers include an enhanced understanding of their illness, formation of social supports (Haywood et al., 2019), and enhanced confidence and competence to contribute to positive change in the health system (Breault et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…People living with mental health conditions have successfully completed multiphase research priority setting initiatives, and engagement from the earliest stages facilitates design of a research agenda that complements clinical efforts. 65 • Embrace research retention practices that facilitate longer-term studies, which can provide outcomes that are more demonstrative of what patients may experience in the real world. Retention is particularly challenging in behavioral health research, 66 and patients can offer useful perspective on study design and implementation to support long-term retention.…”
Section: Recommendations For Research and Practicementioning
confidence: 99%